Long-term results after modified Steel´s triple pelvic osteotomy - Schwarz, Ondřej; Chomiak, Jiří; Dungl, Pavel (Scientific reports, 2025)
Long-term results of modified Steel's triple pelvic osteotomy were evaluated to confirm if this osteotomy is indicated in the era of other redirectional osteotomies and if it can delay total hip arthroplasty (THA). In total, 317 osteotomies were performed on 225 women and 58 men between 1985 and 2012 in one institution. Thirty-four women and three men underwent bilateral surgery. Harris hip scores (HHS) and nonarthritic hip scores (nAHS) and LCE angle, Sharp-Ulmann angle and signs of acetabular version were compared. The results were statistically evaluated using a paired t-test. In total, 55 women and 21 men were contacted. Of these, 35 women and 21 men completed the questionnaires for 68 hips. The follow up ranged from 5 to 32 years (mean 18.5 years). Of the 68 hip joints, 27 had excellent or good results according to HHS and 24 for nAHS. A total of 12 patients underwent THA. Concerning the radiological evaluation, the LCE angle increased from 12° to 34° and Sharp-Ulmann angle decreased from 49° to 36°. Signs of retroversion of the acetabulum occurred in 24 patients without of necessity of surgical treatment. Non-union (five patients) represents the most frequent complication. Steel's triple pelvic osteotomy is still indicated as a safe and effective technique for preserving hip joints and delaying THA. The disadvantage of osteotomy is a relatively long-term recovery time and lower satisfaction compared to THA.
Keywords: osteotomie; Triple pelvic osteotomy; Total hip arthroplasty; Hip Joint; Osteotomy; mladý dospělý; Harris hip score; Arthroplasty, Replacement, Hip; Humans; Male; náhrada kyčelního kloubu; Long-term results; Aged; pánevní kosti; lidé středního věku; ženské pohlaví; Adult; kyčelní kloub; mužské pohlaví; dospělí; Middle Aged; lidé; Follow-Up Studies; následné studie; Treatment Outcome; výsledek terapie; Nonarthritic hip score; senioři; Young Adult; Pelvic Bones; Female